دور المساجد في التفاعل الثقافي في المجتمع الجزائري إبان العهد العثماني - رزاق بعره, مريم; علوان, أمال (جامعة الوادي - University of Eloued, 2022)
يعتبر التعليم والثقافة من بين العناصر المهمة لتقدم المجتمع، واذا سلطنا الضوء على التعليم خلال العهد العثماني ، فنجد أن السلطة الحاكمة لم تكن تتدخل في شؤون التعليم بدليل عدم وجود موظف رسمي لهذا المجال، كالوزير أو الوكيل، ويعود السبب في ذلك إلى تركيز السلطة على المحافظة على استقرار البلاد ، فقد كان التعليم يعتمد على الجهود الفردية للأشخاص والمؤسسات الوقفية، تهدف هذه الدراسة الى معرفة وتقصي الوجه الحقيقي للتعليم والثقافة في إيالة الجزائر إبان العهد العثماني من خلال دور المساجد في نشر الوعي بين فئات المجتمع ، وإبراز التفاعل الثقافي في المجتمع الجزائري خلال العهد العثماني. من أهم النتائج المتوصل إليها المكانة التي حضي بها المسجد في التفاعل الثقافي من خلال الأدوار التي كان يأديها، باعتباره مركزا ديني وعلمي حمل على عاتقه مسؤولية نشر التعليم والثقافة الدينية ولعب دورا هاما في هذا المجال ما جعله قبلة لطلاب العلم. Education and culture are among the important elements for the advancement of society, and if we shed light on education during the Ottoman era; We find that the ruling authority did not interfere in education affairs, as evidenced of that the absence of an official employee in this field, such as a minister or agent, and the reason for this is the authority’s focus on preserving the stability of the country. Education was dependent on the individual efforts of individuals and Endowment institutions, This study aims to know and investigate the true face of education and culture in the province of Algeria during the Ottoman era through the role of mosques in spreading awareness among Segments of society, and showing the cultural interaction in Algerian society during the Ottoman era. One of the most important results reached was the position that the mosque placed in cultural interaction through the roles it was playing, as it was a religious and scientific center. He took on the responsibility of spreading education and religious culture and played an important role in this field, which made it a destination for science students.
مقال
Keywords: المساجد ; التفاعل الثقافي ; التعليم ; المجتمع الجزائري ; العهد العثماني ; الحياة العلمية ; المكتبات ; المناسبات الدينية; Mosques; Cultural interaction; Education; Algerian society; Ottoman era; Scientific life; Libraries; Religious occasions